Making sustainability meaningful: aspirations, discourses and reporting practices. Issue 8 (15th October 2018) - Busco, Cristiano; Giovannoni, Elena; Granà, Fabrizio; Izzo, Maria Federica
Abstract : Purpose: The purpose of this paper is to explore the enabling role of accounting and reporting practices as discourses about sustainability unfold inside organizations. In particular, the authors investigate how managers attempt to connect the concept of "sustainability" to their specific experience, as they seek to make sustainability meaningful (i.e. filling it with unfolding meaning) through accounting and within particular discursive spaces. Design/methodology/approach: The authors rely upon the case of LOGIC, a large international oil and gas company operating in more than 70 countries worldwide. The authors analyze the evolution of discourses concerning sustainability inside the company, as well as the changing accounting and reporting practices, with a particular focus on integrated reporting. Findings: The authors show that accounting and reporting practices (such as integrated reporting within LOGIC) provide the conditions for "sustainability"—as a discursive concept—to become meaningful, while evolving themselves as they are attached to this concept. They do so by enabling individuals (the management team within LOGIC) to connect their diverse experiences and aspirations to the concept of sustainability. Rather than filling sustainability with stable meaning, the authors observed that individuals are attracted by the gaps left by accounting representations, leading to the development of new practices and unfolding meanings within specific discursive spaces. Originality/value: Most of the literature on sustainability accounting and reporting practices concentrate on the need for these practices to mirror what companies do about sustainability. Differently, the authors add to the very few studies on "aspirational" reporting that have emphasized the enabling effects of the gap between what companies say and do about sustainability. The authors do so by demonstrating that accounting is "aspirational" not only because it stimulates corporate efforts toward an imaginary better future, but also because it attracts managers' particular aspirations through its representational gap. The authors show that this gap enables meaningful connections between individuals (their particular experience and aspirations) and "sustainability, " bringing this concept into their specific discursive space and, thereby, leading to the emergence of new practices.